Creative digipreneurs: Artistic entrepreneurial practices in platform-mediated space - Alica Repenning; Anna Oechslen (Digital Geography and Society, 2023)
Digital platforms play an increasingly important role in the everyday work practices of creative entrepreneurs and contribute to how their ventures take shape. Taking this observation as a starting point, this paper aims to explore the entanglement of entrepreneurial, artistic, and creative practices and processes with digital platforms. Drawing on interviews and online observations, the study traces the work practices of two creative producers, a textile designer in Berlin, Germany, and a filmmaker in Bengaluru, India, who both extensively use the social media platform Instagram for their work. Based on the two in-depth case studies, we advance the term creative digipreneurs to reflect the close relationship between the platform, the entrepreneur, and the artistic venture. Creative digipreneurs represent a novel hybrid role that includes the work practices of independent cultural producers, artists, independent entrepreneurs, and creators. This novel perspective allows us to 1) analyse how creative digipreneurs build up a creative venture while relating to people, the local creative scene in the respective cities, and to digital technologies such as Instagram. The platform-mediated situation of the creative digipreneurs allows us to reflect on the entanglement of online and offline spaces in the entrepreneurial artistic process. 2) We demonstrate that while Instagram presents an important opportunity for the creative development, marketing, and sales of the creative product; it also introduces novel constraints.